A very high Q-factor inductor using MEMS technology - Khalid, N.; Shah, K.; Singh, J.; Le, H. P.; Devlin, J.; Zaliman, Sauli, Lt. Assoc. Prof. (SPIE, 2010)
Link to publisher's homepage at http://spiedigitallibrary.aip.org/